2021
DOI: 10.1097/md.0000000000027739
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chloride intracellular channels as prognostic factors correlated with immune infiltration in hepatocellular carcinoma using bioinformatics analysis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Huang et al [36] and Gururaja et al [37] noticed an association between CLIC1 and CLIC 3 immunoexpression and an advanced state of HCC and survival in several different cancers. In the present study, the highest survival rate was found in patients with the desmoplastic and pushing type of LM, with CLIC1 scores of 3 and Avastin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [36] and Gururaja et al [37] noticed an association between CLIC1 and CLIC 3 immunoexpression and an advanced state of HCC and survival in several different cancers. In the present study, the highest survival rate was found in patients with the desmoplastic and pushing type of LM, with CLIC1 scores of 3 and Avastin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…AAK1 is involved in clathrin-mediated endocytosis of chemokine receptors and AAK1-inhibition in mice resulted in increased intratumoral infiltration, supporting an immune-suppressive role for this gene product, as well [ 26 ]. CLIC3 is a chloride intracellular channel protein the gene expression of which has been correlated with low immune infiltration of myeloid dendritic cells (DCs) and poor prognosis in hepatocellular carcinoma [ 27 ]. Therefore, it is possible that a similar immune suppressive role could be exerted in HIF-2-altered UC.…”
Section: Discussionmentioning
confidence: 99%
“…CLICs are a family of multifunctional proteins that can have diverse functions, including chloride transport or the regulation and modulation of gene expression or cytoskeleton structure [206,240]. Intracellular chloride channels are also involved in neurological, pulmonary, and cardiovascular functions and are related to pathologies such as cancer, as they regulate cell cycle and apoptosis [238,241,242].…”
Section: Chloride Intracellular Channels (Clics)mentioning
confidence: 99%